Comprehensive analysis of glycometabolism-related genes reveals PLOD2 as a prognostic biomarker and therapeutic target in gastric cancer - Wanchun Ye; Xiaolei Zhang; Zhongjie Tang; Yufeng Hu; Yuanliang Zheng; Yuping Yuan (BMC Gastroenterology)
Abstract Background Gastric cancer (GC) is one of the leading causes of cancer-related mortality worldwide, with limited therapeutic options and a poor prognosis, particularly in advanced stages. Glycometabolism, a hallmark of cancer, plays a critical role in tumor progression, immune evasion, and response to therapy. However, the specific roles of glycometabolism-related genes and their prognostic and therapeutic implications in GC remain inadequately understood. Methods Transcriptomic and clinical data from GC patients were retrieved from TCGA and GEO databases. Glycometabolism-related genes were identified and analyzed using machine learning algorithms to construct a prognostic model. Functional assays, immune profiling, and pathway enrichment analyses were performed to explore the roles of these genes in tumor progression, immune-modulatory effects, and drug resistance. PLOD2, the gene with the highest prognostic significance, was further investigated to uncover its underlying regulatory mechanisms, roles in immune modulation, and contribution to therapeutic resistance. Results A glycometabolism-related prognostic model consisting of four genes (PLOD2, CHSY3, SLC2A3 and SLC5A1) was developed and validated, effectively stratifying GC patients into high- and low-risk subgroups with distinct survival outcomes. Among these, PLOD2 emerged as the most significant gene, exhibiting strong associations with tumor progression and poor survival. Functional analyses revealed that PLOD2 promotes glycolysis and tumor progression through activation of the PI3K/AKT/mTOR pathway. Immune profiling revealed that PLOD2 overexpression is associated with an immunosuppressive tumor microenvironment, characterized by increased M2 macrophage infiltration and reduced immune activity. Moreover, treatment with rapamycin, an mTOR inhibitor, significantly suppressed PLOD2-mediated proliferation and anchorage-independent growth in GC cells, highlighting the central role of the PI3K/AKT/mTOR pathway in PLOD2-driven oncogenic behaviors. Conclusions This study identifies PLOD2 as a key prognostic biomarker and therapeutic target in gastric cancer. As a central component in a glycometabolism-related model, PLOD2 promotes glycolysis, tumor progression, and immune evasion via the PI3K/AKT/mTOR pathway. The model effectively stratifies patient risk, offering both prognostic utility and therapeutic insight. Targeting PLOD2-mediated pathways may represent a promising strategy for precision therapy and improved clinical outcomes in gastric cancer.